2021
DOI: 10.1001/jamanetworkopen.2021.1955
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of State Cannabis Laws and Rates of Self-harm and Assault

Abstract: Key Points Question Are state cannabis legalization laws with varying degrees of commercialization associated with rates of self-harm or assault injuries? Findings In this cohort study based on health insurance claims data from 75 395 344 beneficiaries between 2003 and 2017, rates of self-harm injuries among males younger than 40 years increased more in states legalizing recreational cannabis dispensaries compared with states without cannabis legalization l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 73 publications
2
33
1
4
Order By: Relevance
“…Varying approaches to implementing similar policies in different places can result in different policy impacts. For example, studies of cannabis legalization often use a binary indicator of legalization, but health impact depends on whether the legalization policy enables retail sales [78][79][80]. For IV studies of the effects of a resource delivered by a policy, it is important to consider whether the consistency assumption holds with respect to the resource variablefor example, would the health benefit of extra income from EITC be similar to the health benefit from extra income due to minimum wage increases.…”
Section: What Effects Are Measured and Among Whom? Measurement Consis...mentioning
confidence: 99%
“…Varying approaches to implementing similar policies in different places can result in different policy impacts. For example, studies of cannabis legalization often use a binary indicator of legalization, but health impact depends on whether the legalization policy enables retail sales [78][79][80]. For IV studies of the effects of a resource delivered by a policy, it is important to consider whether the consistency assumption holds with respect to the resource variablefor example, would the health benefit of extra income from EITC be similar to the health benefit from extra income due to minimum wage increases.…”
Section: What Effects Are Measured and Among Whom? Measurement Consis...mentioning
confidence: 99%
“…Incorrect dates were often used in earlier studies and are now endemic throughout the marijuana and drunk driving literatures. For example, multiple studies list Maryland as becoming a medical marijuana access state as early as October 2003, [24] [32] [36] [37] [38] [39] [40] [41] [42] when the “Darrell Putman Compassionate Use Act” removed the possibility of a jail sentence for marijuana possession if the defendant had a doctor’s note, but did not otherwise protect medical marijuana patients from criminal prosecution. Additionally, some studies previously listed Alabama or Louisiana as medical marijuana states, [42] [43] [44] [45] when “Leni’s Law” in Alabama only decriminalized cannabidiol with low levels of tetrahydrocannabinol (THC) and Louisiana did not allow access to dry marijuana flower until January 1, 2022.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has attempted to measure the consequences of new cannabis liberalization efforts, [22] [23] [24] [25] [26] [27] [28] [29] but there are major disparities in the policy implementation dates among these studies. Recent research has confirmed that suicidal behaviors and other adverse mental health outcomes are correlated with marijuana use disorder (MUD), [30] [31] which can be exacerbated by increasing access to cannabis, [32] but these correlations are also prevalent with other substance use disorders. [18] With marijuana use disorder rates stable since 2002, it is not clear that increasing rates of cannabis consumption through liberalization efforts are leading to adverse population-level mental health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Legalization, on the other hand, is the process of removing all legal prohibitions, allowing cannabis to be available to the adult general population for purchase and use at will, similar to tobacco and alcohol [23]. Currently, a total of 36 states and the District of Columbia have legalized the medical use of cannabis [24]. Although cannabis remains a Schedule 1 drug, the Rohrabacher-Farr amendments prohibit federal prosecution of individuals complying with state medical cannabis laws.…”
Section: Legalization and The Rise Of Medical Cannabis Usementioning
confidence: 99%